2022
DOI: 10.1111/cch.12986
|View full text |Cite
|
Sign up to set email alerts
|

The glue that keeps everybody together: Peer support in mothers of young children with special health care needs

Abstract: Background:The first years following diagnosis may be particularly challenging for parents and peer support from other parents of children with special health care needs may buffer their stress.Methods: This qualitative interview study sought to explore the impact of early access to parental peer support and whether it leads to positive adaptation and improved family well-being.Results: Five mothers of young children with special health care needs from peer support organizations in two northern US states parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In light of the effects of COVID-19, there is a national emphasis on the need for social and emotional support to address increased caregiver distress [ 31 – 33 ]. Caregivers can often provide the highest quality healthcare, yet the reality of current support among CMC and their families is alarming [ 18 , 19 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In light of the effects of COVID-19, there is a national emphasis on the need for social and emotional support to address increased caregiver distress [ 31 – 33 ]. Caregivers can often provide the highest quality healthcare, yet the reality of current support among CMC and their families is alarming [ 18 , 19 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also demonstrated that parent‐to‐parent support provides fertile ground for parents and peers to develop new, positive visions for the future and opportunities for individuals to thrive (Bray et al, 2017). Like Dodds and Walch (2022), we view peer support through a family resilience lens. Therefore, we have organized our findings to demonstrate how the relationships and underlying processes of peer support can be understood within a family resilience framework.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of studies that have identified possible pathways in which resilience can be understood in these families (Gunty, 2020; Leone et al, 2016). Others have previously demonstrated how family resilience frameworks are relevant to the qualitative experience of parents involved in peer support contexts (Dodds & Walch, 2022). Our present study represents a contribution to this literature insofar as we propose a theoretical model demonstrating how peer support and family resilience intersect.…”
Section: Introductionmentioning
confidence: 99%
“…IP2PS is defined as individualized support provided in a one‐on‐one setting, as opposed to peer‐based support offered in group settings. It is delivered by a parent with similar experiences caring for a child with BBDD (Dodds & Walch, 2022). During these sessions, parents of a child with BBDD have conversations and share experiences in order to support each other (Wong & Shorey, 2022).…”
Section: Introductionmentioning
confidence: 99%